2015
DOI: 10.1002/mnfr.201500409
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of oleuropein attenuates cisplatin‐induced acute renal injury in mice through inhibition of ERK signaling

Abstract: The results of the current study suggest that oleuropein attenuated CP-induced acute renal injury, which was mediated through the inhibition of ERK signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 50 publications
6
30
0
Order By: Relevance
“…More specifically, Itkonen et al, showed that UDP-GlcNAc is activated in PC-3 prostate cancer cells and can act as a modulator of prostate cancer growth, which reinforces the notion that these often overlooked protein modifications have the potential to improve risk stratification and therapeutic strategies in patients with prostate cancer [37]. Finally, our results agree with those, recently reported, suggesting the beneficial effects of oleuropein against cancer, ageing, neurodegeneration, diabetes and diseases implying autophagy dysfunction [38,39]. Further understanding of the molecular mechanisms which are activated in response to different stimuli is therefore important towards the pharmaceutical development of novel treatment methods for prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, Itkonen et al, showed that UDP-GlcNAc is activated in PC-3 prostate cancer cells and can act as a modulator of prostate cancer growth, which reinforces the notion that these often overlooked protein modifications have the potential to improve risk stratification and therapeutic strategies in patients with prostate cancer [37]. Finally, our results agree with those, recently reported, suggesting the beneficial effects of oleuropein against cancer, ageing, neurodegeneration, diabetes and diseases implying autophagy dysfunction [38,39]. Further understanding of the molecular mechanisms which are activated in response to different stimuli is therefore important towards the pharmaceutical development of novel treatment methods for prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The oleuropein doses used in the previous studies ranged from 2.5 mg/kg to 300 mg/kg . Even though there are limited studies regarding the effect of oleuropein in rats, all reported studies demonstrated beneficial effects of oleuropein in studied doses . Furthermore, there is no accepted therapeutic dose for oleuropein.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings fill a gap, considering that data on the dose‐dependence of the healthy effects of olive polyphenols are not available, in spite of the interest of the issue taking into account the reduced bioavailability of these molecules once given orally. The only data refer to protection against cisplatin‐induced acute renal injury in mice and to the dose‐dependent suppression of intracellular triglyceride accumulation in 3 T3 pre‐adipocytes during differentiation to adipocytes whereas no data are available on neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%